Temporary Denosumab Discontinuation Promotes Bone Healing of Osteonecrosis of the Jaw and Minimizes the Invasiveness of Surgery: A Case Presentation - Giordana Bettini; Giorgia Saia; Federica Benetello; Alberto Bedogni (MDPI AG, 2022)
Denosumab has proved effective at low doses in increasing bone mineral density in osteoporosis patients. In contrast to high-doses antiresorptive therapy, denosumab has a transient effect on the inhibition of the bone remodeling process, suggesting that denosumab-related osteonecrosis is a self-limiting disease, with a high curative potential of surgery when performed after a proper duration of receptor activator of nuclear factor-kB ligand (RANKL) inhibitor suspension. We report the long-term clinical and radiological (Computed Tomography-CT scan) data of a patient affected by secondary osteoporosis (cancer treatment-induced bone loss-CTIBL for metastatic breast cancer) who underwent surgical treatment for stage II denosumab-related osteonecrosis of the upper maxilla 7 months after denosumab suspension. A minimally invasive approach was performed with the extraction of the first right upper molar and debridement of the surrounding alveolar bone. After surgery, the patient was followed up at three-month intervals up to 1 year, and clinical and radiological data (CT scan) were recorded at each follow-up for the early detection of signs of recurrent disease. The mucosal healing remained stable in the long term, with radiological signs of bone remodeling in the post-operative site since the 6-month follow-up. The presented case strengthens the hypothesis that denosumab induces temporary alterations of bone turnover with a predictable curative effect of minimal surgical procedures in cases of denosumab-related osteonecrosis of the jaw.